The Role of Hematopoietic Stem-Cell Transplantation in First Remission in Pediatric Acute Lymphoblastic Leukemia: A Narrative Review - Neel S. Bhatt; Rachel Phelan; Michael J. Burke (Mazandaran University of Medical Sciences, 2017)
Context Survival after allogeneic hematopoietic stem-cell transplantation (HSCT) for children with hematologic malignancies including acute lymphoblastic leukemia (ALL) continues to improve in part due to advancement in HLA typing and enhanced supportive care. Despite improved outcomes with HSCT, the decision to offer it in first remission (CR1) in children with ALL remains a topic of debate and uncertainty. This review aims to discuss the role of HSCT in CR1 for children with high-risk subsets of ALL in the current era. Evidence Acquisition A thorough review of the literature was performed using electronic databases: PubMed, Google Scholar, and bibliographies. Studies focusing on high-risk subsets of ALL (Primary Induction Failure, Severe Hypodiploidy, Philadelphia-chromosome positive ALL, T-Cell ALL, Infant ALL, ALL with persistent minimal residual disease (MRD), and Philadelphia-like ALL) were included. Publications in non- English language were excluded. Results Based on our review of the current literature, HSCT should be considered in first remission for patients with primary induction failure, severe hypodiploidy, T-cell ALL with poor response, high-risk infant ALL, and persistently positive MRD. In contrast, HSCT in CR1 may not be warranted for patients with early T-cell progenitor ALL or Philadelphia-chromosome positive ALL. Further data are needed to make specific recommendations regarding Philadelphia-like ALL. Conclusions As our understanding of high-risk leukemia biology continues to develop, the role of HSCT in ALL CR1 will need to be revisited.